Effectiveness of outcome-based approach to design contents for training secondary school English teachers in Laos - Lakaisone Saiyachit (Journal of Green Learning, 2022)
This research aimed at evaluating effectiveness of an outcome-based approach for redesigning contents (training tasks, instructions, and assessments) of a teacher training program. Research participants were three English secondary school teachers. The effectiveness was evaluated by assessing abilities of in-service teachers to use 15 student-centered teaching techniques to design activities to teach English, appropriateness of training contents and usefulness of abilities gained from the training. Therefore, the data were gathered by assessing trainees’ abilities during and after training and interviewing them at the end of the training. The findings show that all of the in-service teachers have gained high abilities to use the 15 students centered teaching techniques for designing activities to teach English. The findings from interview show that the training contents are suitable for training the new teaching skills and they confident to use them. Therefore, high training achievement and very positive opinions found in this research confirm that outcome-based approach is effective to use for designing contents of training program.